Peptide-directed assembly of single-helical gold nanoparticle superstructures exhibiting intense chiroptical activity - Merg, A; Boatz, J; Mandal, A; Zhao, G; Mokashi-Punekar, S; Liu, C; Wang, X; Zhang, P; van der Wel, P; Rosi, N (American Chemical Society, 2016)
Chiral nanoparticle assemblies are an interesting class of materials whose chiroptical properties make them attractive for a variety of applications. Here, C18-(PEPAu(M-ox))2 (PEPAu(M-ox) = AYSSGAPPM(ox)PPF) is shown to direct the assembly of single-helical gold nanoparticle superstructures that exhibit exceptionally strong chiroptical activity at the plasmon frequency with absolute g-factor values up to 0.04. Transmission electron microscopy (TEM) and cryogenic electron tomography (cryo-ET) results indicate that the single helices have a periodic pitch of approximately 100 nm and consist of oblong gold nanoparticles. The morphology and assembled structure of C18-(PEPAu(M-ox))2 are studied using TEM, atomic force microscopy (AFM), Fourier transform infrared (FTIR) spectroscopy, circular dichroism (CD) spectroscopy, X-ray diffraction (XRD), and solid-state nuclear magnetic resonance (ssNMR) spectroscopy. TEM and AFM reveal that C18-(PEPAu(M-ox))2 assembles into linear amyloid-like 1D helical ribbons having structural parameters that correlate to those of the single-helical gold nanoparticle superstructures. FTIR, CD, XRD, and ssNMR indicate the presence of cross-β and polyproline II secondary structures. A molecular assembly model is presented that takes into account all experimental observations and that supports the single-helical nanoparticle assembly architecture. This model provides the basis for the design of future nanoparticle assemblies having programmable structures and properties.